The Effect of Stirring Time on the Physical Properties of Cream with Coconut Water Cocos Nucifera L. as the Active Ingredient - Lia Amelia; Kusnadi; Muladi Putra Mahardika (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Coconut water (Cocos nucifera L.) contains natural compounds that are beneficial for skin health, making it a promising ingredient in cream formulations. Mixing duration is an important factor in cream preparation because it affects homogeneity, stability, and texture. This study evaluated the effect of mixing times (15, 20, and 25 minutes) on the physical properties of coconut water–based creams. The formulations were tested for organoleptic properties, homogeneity, pH, spreadability, adhesion, viscosity, and stability. Results showed that mixing duration influenced viscosity, spreadability, and homogeneity, while pH remained within the normal skin range (4.5–6.5). A mixing time of 20 minutes produced the most optimal cream characteristics. Therefore, proper mixing duration is essential for achieving stable and high-quality cream formulations. Keywords: Coconut Water, Cream Formulation, Mixing Duration, Physical Properties, Stability.